The spatio-temporal distribution and transport of suspended sediment in Laizhou Bay: Insights from hydrological and sedimentological investigations - Xie, Bo; Bao, Rui; Yin, Dongxiao; Zhu, Longhai; Hu, Rijun; Cai, Weiwei; Liu, Tao; Lin, Chaoran; Lu, Pengfei (Frontiers in Earth Science, 2022)
Suspended sediment transport and deposition are crucial physical processes controlling the geomorphological evolution of estuaries and bays. Specially, under the context of worldwide coastal erosion, knowledge of the spatio-temporal distribution of suspended sediment concentration (SSC) and its associated sediment load have become increasingly important for bay management. However, our understanding of the mechanisms of suspended sediment dynamics continues to be hampered by the lack of high-resolution observations. Here, we present a study of the transport mechanisms and controlling factors of suspended sediment over Laizhou Bay. For this, we conducted continuous measurements of SSC, salinity, temperature, and flow velocity at nine stations throughout Laizhou Bay for one 25-hour period during each of the spring and moderate tides. Based on these data, residual current, gradient Richardson numbers, and suspended sediment flux were calculated. Our results indicate that a strong current field occurs near the Yellow River mouth, corresponding to the zone with high SSC. The overall diffusion characteristics of suspended sediment are controlled by the tidal current field. Furthermore, our findings suggest that different degrees of stratification occur in the water column, which inhibit the effective vertical diffusion of suspended sediment; Higher water temperature was the main cause of stronger water column stratification of spring tide than moderate tide. Finally, our results reveal that the type of seabed sediment is an important factor controlling SSC by influencing resuspension flux. We conclude that the primary mechanisms controlling suspended sediment transport in Laizhou Bay are advection and tidal pumping, especially advection. Our research provides both a foundational reference for the sediment source-to-sink process from the Yellow River to the sea, as well as guideline implications for coastal engineering construction and channel dredging.